Self-perceived health of ultra poor women: The effect of an inclusive development intervention - Prakash, Vivek A.; Rana, AKM Masud (BRAC Research and Evaluation Division and Aga Khan Foundation Canada, 2022)
In 2002, BRAC launched a targeted and comprehensive development program called Challenging the Frontiers of Poverty Reduction: Targeting the Ultra Poor (CFPR/TUP) aimed at the poorest of the poor, who have often been excluded from other development initiatives. This study examines changes in the self-reported health status of these ultra-poor women in northern Bangladesh over a period of one and half years since the launch of this program. The data for this study come from a baseline survey performed in 2002 and a follow-up survey from 2004. The ultra-poor women selected for the CFPR/TUP program fared far better than those not included in the program with better self-reported health status. Program effects remain positive and significant after controlling for marital status, education, age, previous health, disability, occupation, sanitary knowledge and behaviour, family planning, and location. We conclude that the CFPR/TUP program has a significant effect on women’s health, highlighting the importance of development as a holistic process with various components.